O wymowie "Chorągwi sauromatckiej" Marcina Paszkowskiego = The message of Sauromatian Flag (Chorągiew sauromatcka) by Marcin Paszkowski - Sztyber, Radosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper is an attempt to present the real message of Sauromatian Flag (Chorągiew sauromatcka) by Marcin Paszkowski. The XVII century text is considered to be an eulogy of the whole Polish army that had beaten the forces of Ottomans' Empire in 1621 at Khotyn (Chocim). However a lot of obvious historical facts contradicts such a point of view for a significant part of Polish troops has never reached the battlefield near the Dniester River at all.
Keywords: "Chorągiew sauromatcka w Wołoszech, to jest pospolite ruszenie i szczęśliwe zwrocenie Polakow z Wołoch w roku teraźniejszym 1621"; Paszkowski, Marcin - twórczość; literatura polska - historia; 17 w.